Gestão de recursos externos em projetos na área social: o caso do Projeto de Serviços Básicos de Saúde no Nordeste - PNE I - Leal, Patrícia Raupp Machado (2001)
The following paper analyses the managerial and administrative aspects of a project named Projeto de Serviços Básicos de Saúde no Nordeste (PNE I) - initiated in the 80¿s and has been funded by the International Development and Reconstruction Bank (IDRB) ¿ for the construction of a series of lessons and recommendations to be observed along the formulation, implementation and assessment of projects performed under external financing. During the Project time the most important and deep changes and innovations have occurred involving the national politics for health, which have been mostly decisive at directing the Project, specially concerning the organization of services with emphasis to the process of decentralization as well as the participation of the organized society as a tool of social control. The expectations towards the publicizing and the dissemination of the paper presented are laid upon the warranty that the recommendations hereby given shall, effectively, contribute for the decrease of unwanted results and for the magnification of variables to be considered in projects with the scope and characteristics similar to PNE I.